Lithostratigraphic classification of the Tsodilo Hills Group: a Palaeo- to Mesoproterozoic metasedimentary succession in NW Botswana - Wendorff, Marek; Świąder, Andrzej (Geology, Geophysics and Environment, 2020)
The Tsodilo Hills Group strata exposed in the Tsodilo Hills are an association of metaarenites, metaconglomerates, quartz-mica schists, sandstone, red siltstone and sedimentary breccia deposited on an open siliciclastic marine shelf between the Late alaeoproterozic and Late Mesoproterozoic, and outcropping in NW Botswana. The uccession is dominated by three micaceous quartzite units interlayered with subordinate lenses and wedges of other rock types. Facies gradients from S to N are expressed by: decreasing content of muscovite at all levels of metasediment organisation from thin wedge-shaped units to thick quartzite complexes, as well as a decrease in pebble content and increase in arenaceous matrix in some metaconglomerate beds, matching regional palaeotransport direction. Well-rounded pebbles of extrabasinal rocks are flat, suggesting redeposition from a beach environment. Lenticular conglomeratic bodies with erosional lower boundaries represent infills of local incisions in the sandy bottom sediments. The abundance of laterally discontinuous lithological units reflects shelf palaeotopography controlled and modified by deposition and migration of large bed forms, ranging from megaripple marks (or submarine dunes) to sand waves. Deposition was influenced by tides and two regressive events. The older regression resulted in a marker unit of tidal mudflat-related red-bed facies: mudstone, siltstone, channel-fill sandstone and sedimentary breccia. The second regression is indicated by a tabular conglomerate marker reflecting increased input of coarse terrigenous material.